2015
DOI: 10.1080/15384101.2015.1064568
|View full text |Cite
|
Sign up to set email alerts
|

ATF7 is stabilized during mitosis in a CDK1-dependent manner and contributes to cyclin D1 expression

Abstract: The transcription factor ATF7 undergoes multiple post-translational modifications, each of which has distinct effects upon ATF7 function. Here, we show that ATF7 phosphorylation on residue Thr112 exclusively occurs during mitosis, and that ATF7 is excluded from the condensed chromatin. Both processes are CDK1/cyclin B dependent. Using a transduced neutralizing monoclonal antibody directed against the Thr112 epitope in living cells, we could demonstrate that Thr112 phosphorylation protects endogenous ATF7 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The Ccnd1 gene is regulated at the transcriptional and translational levels (27)(28)(29). We found that Ccnd1 transcription is dependent on Insm1 dosage, and the protein level is also decreased in b-cells of Insm +/lacZ mice.…”
Section: Discussionmentioning
confidence: 74%
“…The Ccnd1 gene is regulated at the transcriptional and translational levels (27)(28)(29). We found that Ccnd1 transcription is dependent on Insm1 dosage, and the protein level is also decreased in b-cells of Insm +/lacZ mice.…”
Section: Discussionmentioning
confidence: 74%
“…Notably, there is increasing evidence indicating that ATF7 may function to regulate proliferation and the cell cycle in various cancers. For example, ATF7 was shown to promote cell cycle progression by regulating cyclin D1, as well as the expression of stress‐activated MAPK in G1 and S phases and Cdk1‐cyclin B1 in the G2/M phase . In addition, ATF7 has been shown to form a heterodimeric complex with the AP‐1 family member, c‐jun, through its C‐terminal leucine‐zipper region, which functions to promote cell growth .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ATF7 was shown to promote cell cycle progression by regulating cyclin D1, as well as the expression of stress-activated MAPK in G1 and S phases and Cdk1-cyclin B1 in the G2/M phase. 26,27 In addition, ATF7 has been shown to form a heterodimeric complex with the AP-1 family member, c-jun, through its C-terminal leucine-zipper region, which functions to promote cell growth. 28 Mouse knockout studies have further shown that ATF7 knockout, combined with key mutations in ATF2, results in embryonic lethality that is characterized by high levels of apoptosis in developing hepatocytes and hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a monoclonal antibody (mAb) directed against the activating transcription factor 7 (ATF7) was chemically coupled to a thiol-containing synthetic E3 peptide. This antibody was chosen because it recognizes endogenous ATF7 (1A7) bound to the chromatin .…”
Section: Resultsmentioning
confidence: 99%
“…The co-localized signal was dependent of the specific interaction between E3 and K3 peptides as no signal was detectable in the presence of an unrelated V H H without K3 or in the absence of con1-mCherry-E3 expression. Finally, a monoclonal antibody (mAb) directed against the activating transcription factor 7 (ATF7) 21 was chemically coupled to a thiol-containing synthetic E3 peptide. This antibody was chosen because it recognizes endogenous ATF7 (1A7) 22 bound to the chromatin.…”
Section: In Cellulo Conjugation Of Macromolecules Via E3 and K3 Peptidesmentioning
confidence: 99%